Migrasi dalam Perspektif Sosio Teologi Kristen: Krisis Pengungsi Irak-Suriah di Eropa Barat - Gandi Wibowo (LPPM STT Baptis Kalvari, 2022)
Migration with various motifs in it is a phenomenon that has long been known in the Bible. The migration of the Terah family, Jacob's family, Naomi's family and even Joseph's small family are examples of migration written in the scriptures. Most of Paul and Peter's letters are also addressed to diaspora Christians. In fact, Christians are foreigners on this earth. The dynamics experienced by them as migrants are also experienced by migrants in the modern era. Migration of people from conflict countries to the European Union in 2015 is interesting to study with the problems in it. Migrants experience social pressures and cultural clashes even though the European Union is also subject to UN Conventions and the EU Declaration of Human Rights. Migration carried out can be in the form of skilled migration, refugees (refugees) or asylum seekers (asylum seekers). The cultural clash between local residents and immigrants in Europe is a test of the value of European justice and freedom. The discourse that occurs tries to present the problem more clearly and objectively.